Crystal Growth and Characterization of the Mixed‐Cation Rb+/[XeF5]+ and Cs+/[XeF5]+ Salts. Issue 21 (29th March 2017) - Mazej, Zoran; Goreshnik, Evgeny
Abstract : Reactions between ASbF6 (A = Rb, Cs) and [XeF5 ][SbF6 ] in anhydrous HF in 1:1 molar ratios yielded isotypic A[XeF5 ][SbF6 ]2 compounds upon crystallization. The A[XeF5 ][SbF6 ]2 (A = Rb, Cs) salts crystallize in two crystal modifications at low (α phase, 150 K) and ambient (β phase, 296 K) temperatures. Similar reactions between CsBiF6 and [XeF5 ][SbF6 ] (1:1) yielded mixed‐cation/mixed‐anion compounds Cs[XeF5 ][Bi x Sb1– x F6 ]2 ( x = 0.37–0.39). One of the two crystallographic positions of the pnictogen atoms is randomly occupied with both Bi (ca. 40 %) and Sb (ca. 60 %) atoms. The simultaneous presence of both [SbF6 ] – and [BiF6 ] – has been confirmed by Raman spectroscopy. The low‐ and high‐temperature phases of Bi/Sb mixed‐anion compounds are isotypic with the corresponding A[XeF5 ][SbF6 ]2 (A = Rb, Cs) phases. No reactions were observed in the AAsF6 (A = Rb, Cs)/[XeF5 ][AsF6 ], ASbF6 (A = K, [H3 O] + )/[XeF5 ][SbF6 ], and KBF4 /[XeF5 ][SbF6 ] systems. In the CsBF4 /[XeF5 ][SbF6 ] system, a metathetical reaction occurred, leading to [XeF5 ][BF4 ] (orthorhombic at 150 K, Pbca space group) and CsSbF6 . The latter reacted further with [XeF5 ][SbF6 ], yielding Cs[XeF5 ][SbF6 ]2 . A double‐displacement reaction also proceeded between Cs2 MnF6 and [XeF5 ][SbF6 ] to give [XeF5 ]2 [MnF6 ] and CsSbF6 . The reaction between CsPF6 and [XeF5 ][SbF6 ] proceeded with the displacement of the weaker Lewis acid, PF5, with the stronger one, SbF5, resulting in [Xe2 F11 ][SbF6 ] and CsSbF6, which reacted with [XeF5 ][SbF6 ] to yield Cs[XeF5 ][SbF6 ]2 . Abstract : Reactions of APnF6 (A = [H3 O] +, K, Rb, Cs; Pn = P, As, Sb, Bi), ABF4 (A = K, Cs), and Cs2 MnF6 with [XeF5 ][PnF6 ] (Pn = As, Sb) may end in one of three ways: no reaction; a double‐displacement reaction; or formation of A[XeF5 ][SbF6 ]2 (A = Rb, Cs) and Cs[XeF5 ][Bi x Sb1– x F6 ]2 ( x = 0.37–0.39). All three compounds crystallize in two crystal modifications at low (150 K) and at high (296 K) temperatures.